[Students in Yosemite Hall dorm room] (1977)
The room includes a bunk bed setup, with apparently hand-made bunk bed and speaker system, one sitting on a couch with another standing among multiple hanging plants. The walls are covered in framed pictures or illustrations, a poster for 'Design Village 77', possibly architecture students. Several other hand-drawn posters hanging on the wall, with a book open on the desk.